2006
DOI: 10.1021/tx060023c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Hemoglobin Adduct in Sprague Dawley Rats Exposed to Atrazine

Abstract: Atrazine (2-chloro-4-[ethylamino]-6-[isopropylamino]-1,3,5-triazine) is one of the most commonly used herbicides in North America and is frequently detected in ground and surface waters. This research investigated possible covalent modifications of hemoglobin following in vivo exposures to atrazine in Sprague Dawley (SD) rats and in vitro incubations with diaminochlorotriazine. SD rats were exposed to 0, 10, 30, 100, and 300 (mg atrazine/kg)/day for 3 days via oral gavages, and blood was drawn at 0 h, 24 h, 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…These data suggested that ATR is perhaps the primary compound that acutely affects the brain and that metabolism of ATR, at least in terms of its acute effects on the brain, is a detoxication mechanism. However, recent reports indicated that both ATR and DACT can covalently react with proteins forming stable protein adducts (Dooley et al, 2006(Dooley et al, , 2008. Several proteins were identified in these studies that were adducted by DACT, but the functional consequence of this adduction is currently unknown.…”
Section: Ross Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggested that ATR is perhaps the primary compound that acutely affects the brain and that metabolism of ATR, at least in terms of its acute effects on the brain, is a detoxication mechanism. However, recent reports indicated that both ATR and DACT can covalently react with proteins forming stable protein adducts (Dooley et al, 2006(Dooley et al, , 2008. Several proteins were identified in these studies that were adducted by DACT, but the functional consequence of this adduction is currently unknown.…”
Section: Ross Et Almentioning
confidence: 99%
“…Thus, some of the effects of ATR exposure on the thymus may be indirect, i.e., mediated by activation of the stress axis, which is observed after acute ATR exposure (Pruett et al, 2003). On the other hand, because ATR and DACT were detectable in the spleen, their ability to form protein adducts (Dooley et al, 2006(Dooley et al, , 2008 may play a role in the longerlasting effects of ATR exposure on the spleen (Filipov et al, 2005).…”
Section: Ross Et Almentioning
confidence: 99%
“…Despite its relatively short half-life in the adult rat (< 1 day), many laboratories have shown that ATR administration adversely affects the endocrine system and reproductive tissue development in the rat (reviewed by Dooley et al 2006). Long-term dietary exposure to 400 ppm ATR (~ 22.5 mg/kg) caused an early onset of mammary tumors in Sprague-Dawley rats, and the appearance of tumors was mediated by ATR-induced premature reproductive aging (Eldridge et al 1994b, 1998, 1999a, 1999b).…”
mentioning
confidence: 99%
“…DACT is reactive towards exposed cysteine residues in vitro forming stable covalent adducts through a non-enzymatic nucleophilic substitution reaction at the chlorine moiety. 20 Numerous DACT-adducted proteins have been identified in the pituitary and hypothalamus in previous studies with ATRA exposed rodents suggesting widespread protein modification. 14,21 Nearly all of the identified modified proteins share the common characteristic of exposed cysteine residues.…”
Section: Discussionmentioning
confidence: 97%